Optimization and kinetics of citronella oil extraction by ohmic heated hydro distillation - Hamzah, Muhammad Hazwan (2013)
Citronella grass is an aromatic plant with a variety of applications and tremendous economic potentials. The essential oil from the citronella grass has a variety of uses such as in traditional medication, perfume industry and soap manufacturing. A proposed method for citronella oil extractionwas developed with the application of ohmic heated hydrodistillation. The main objective of this research was to determine the parameters of the citronella oil extraction to achieve maximum oil yield by ohmic heated hydro distillation. The parameters affecting citronella oilextraction by ohmic heated hydro distillation such as powerinput, extraction time, solvent to solid ratio and crushing frequency were investigated.The optimum parameters were found at a power input of 77 V up to the boiling point of water and followed by 50 V until the end of extraction, 2 hours extraction time, a solvent to solid ratio of 3:1 and a crushing frequency of once. The optimized parameters were then applied to hydro distillation and steam distillation. Thekinetics of extraction was proposed and validated based on asecond-order model.The maximum amount of yield of optimized parameters in kinetic study by ohmic heated hydro distillation was 7.64 mL/kWh in comparison with hydro distillation and steam distillation methods that resulted oil yield 3.87 mL/kWh and 1.69 mL/kWh, respectively. The proposed model fitted well with the experimental data showed that the coefficient of determination, R2 more than 0.97. The chemical, physical and biological properties of citronella oil and leaves extracted using three different extraction methods were also determined. Gas chromatography-mass spectrometry analysis found that the major constituents of citronella oil for the different extraction methods were citronellal, citronellol and geraniol. The results for specific gravity and refractive index at 20 °C were ranged from 0.8879 to 0.8916 and 1.4671 to 1.4743, respectively. The citronella oil colour intensity in terms of red and yellow units was 2.0 Y to 0.7R 4Y. Scanning electronmicrographs of citronella grass showed some microfractures and cell wall became less rigidity for ohmic heated hydro distillation. Results of this research revealed that ohmic heated hydro distillation could be introduced as an alternative technology to conventional methods.